Characterization of Visual Field Loss Over 4 Years in the Rate of Progression in USH2A-Related Retinal Degeneration (RUSH2A) Study - Duncan, Jacque L.; Maguire, Maureen G.; McDaniel, Lee S.; Doucet, Nicole R.; Audo, Isabelle; Ayala, Allison R.; Cheetham, Janet K.; Cheng, Peiyao; Durham, Todd A.; Huckfeldt, Rachel M.; Hufnagel, Robert B.; Jayasundera, K. Thiran; et al. (American journal of ophthalmology, 2025)
To report visual field loss using static perimetry (SP) and kinetic perimetry (KP) over 4 years in the Rate of Progression of USH2A-related Retinal Degeneration (RUSH2A) study. Prospective, observational cohort study. Participants had USH2A-related rod-cone degeneration, visual acuity ≥20/80, and KP III4e ≥10° at baseline in the study eye. Preserved cohorts with baseline visual fields sufficient to detect progression were identified. Participants were examined annually through 4 years. Mixed-effects models were used to estimate the annual, standardized rate, and percentage rates of change. SP measures included hill of vision (total: VTOT, central 30°: V30, and peripheral: VPERIPH) and centrally weighted mean sensitivity (MScw). Percentages with 4-year progression exceeding the coefficient of repeatability (CoR) and with change meeting Food and Drug Administration (FDA)-recommended criteria were estimated. KP seeing area (dB-steradian (sr)/degree) for I4e, III4e, and V4e isopters was calculated. The average decline with SP (95% CI) was 1.94 (1.62, 2.25) dB-sr/y for VTOT, 0.54 (0.45, 0.62) dB-sr/y for V30, 1.37 (1.11, 1.63) dB-sr/y for VPERIPH, and 0.56 (0.48, 0.64) dB/y for MScw. Average percentage decline per year was 8.6% (7.2, 10.0) for VTOT, 6.4% (5.3, 7.5) for V30, 13.6% (10.4, 16.7) for VPERIPH, and 5.6% (4.7, 6.4) for MScw. The standardized rate of change was greatest at −1.35 for MScw. Rates were higher in the preserved cohorts. Progression exceeding the CoR was 18% (11, 28) for VTOT, 21% (13, 31) for V30, 21% (13, 31) for VPERIPH and 17% (10, 27) for MScw. Progression exceeding an FDA-recommended threshold was 5% (2%, 12%) for all SP points and 45% (35%, 55%) for functional transition points. Average KP annual percentage decline was 13.1% (7.5, 18.5) for I4e, 12.1% (8.1,15.9) for III4e, and 9.2% (6.3,12.0) for V4e. All quantitative perimetry measures declined over 4 years. Progression was greater than the CoR in a relatively low percentage of eyes (17%-21%); 45% exceeded the FDA-recommended threshold when only functional transition points were considered. Standardized rate of change was greatest for MScw. These measures are useful characterizations of vision loss in USH2A-related retinal degeneration.